The Effect of an Innovative Financing and Payment Model for Tuberculosis Patients on Health Service Utilization in China: Evidence from Hubei Province of China - Jiang, Junnan (Int J Environ Res Public Health, 2019)
Background: Tuberculosis (TB) remains a major social and public health problem in China. The “China–Gates TB Project” started in 2012, and one of its objectives was to reduce the financial burden on TB patients and to improve access to quality TB care. The aims of this study were to determine if the project had positive impacts on improving health service utilization. Methods: The ‘China–Gates TB Project’ was launched in Yichang City (YC), Hubei Province in April 2014 and ended in March 2015, lasting for one year. A series of questionnaire surveys of 540 patients were conducted in three counties of YC at baseline and final evaluations. Inpatient and outpatient service utilization were assessed before and after the program, with descriptive statistics. Propensity score matching was used to evaluate the impact of the China–Gates TB Project on health service utilization by minimizing the differences in the other characteristics of baseline and final stage groups. Focus group discussions (FGDs) were held to further enrich the results. Results: A total of 530 patients were included in this study. Inpatient rates significantly increased from 33.5% to 75.9% overall (p < 0.001), with the largest increase occurring for low income patients. Outpatient visits increased from 4.6 to 5.6 (p < 0.001), and this increase was also greatest for the poorest patients. Compared with those who lived in developed counties, the overall increase in outpatient visits for illness in the remote Wufeng county was higher. Conclusions: The China–Gates TB Project has effectively improved health service utilization in YC, and poor patients benefited more from it. TB patients in remote underdeveloped counties are more likely to increase the use of outpatient services rather than inpatient services. There is a need to tilt policy towards the poor, and various measures need to be in place in order to ensure health services utilization in undeveloped areas.